Hemoglobin Variants as Targets for Stabilizing Drugs - Miroslava Žoldáková; Michal Novotný; Krishna P. Khakurel; Gabriel Žoldák (Molecules)
Hemoglobin is an oxygen-transport protein in red blood cells that interacts with multiple ligands, e.g., oxygen, carbon dioxide, carbon monoxide, and nitric oxide. Genetic variations in hemoglobin chains, such as those underlying sickle cell disease and thalassemias, present substantial clinical challenges. Here, we review the progress in research, including the use of allosteric modulators, pharmacological chaperones, and antioxidant treatments, which has begun to improve hemoglobin stability and oxygen affinity. According to UniProt (as of 7 August 2024), 819 variants of the α-hemoglobin subunit and 771 variants of the β-hemoglobin subunit have been documented, with over 116 classified as unstable. These data demonstrate the urgent need to develop variant-specific stabilizing options. Beyond small-molecule drugs/binders, novel protein-based strategies—such as engineered hemoglobin-binding proteins (including falcilysin, llama-derived nanobodies, and α-hemoglobin-stabilizing proteins)—offer promising new options. As our understanding of hemoglobin’s structural and functional diversity grows, so does the potential for genotype-driven approaches. Continued research into hemoglobin stabilization and ligand-binding modification may yield more precise, effective treatments and pave the way toward effective strategies for hemoglobinopathies.